Studi Literatur: Pengaruh Asset And Liabilities Management Terhadap Perbankan - Sukmawati Ema; Aprelia Tertadirja; Carmel Meiden (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2023)
This study describes Asset Liability Management of the Company through surveyed journals in Indonesia from 2017 to 2022. The purpose of this study is to add and develop research or articles on Asset and Liability Management (ALMA) published in Indonesian journals. The samples obtained were 25 articles. This research uses a systematic literature study method, with a PoP (Publish or Perish) application. From this literature study, we conclude that the operation of the Asset and Liability Management (ALMA) function can optimize the structure of a bank's balance sheet in a competitive financial market environment through bank liquidity management policies while maintaining quota and liquidity status. These include primary and secondary reserves, gap management by managing and controlling the gap between assets and liabilities to maximize net profit margin (NIM), exchange rate management by maximizing exchange rate differential returns, investment management and returns through investment decisions in a bank's fortopolio.